2019
DOI: 10.1080/21691401.2019.1687499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of anti-PD-1/PD-L1 treatments in non-small cell lung cancer (NSCLC)

Abstract: Aims: The present study was performed to investigate the efficacy and safety of anti-programmed death-1 (PD-1)/programmed death-ligand-1 (PD-L1) treatments in non-small cell lung cancer (NSCLC). Methods: The potential articles were searched from Pubmed and Embase. The end points included overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and adverse events. p < .05 or I 2 ! 50% meant obvious heterogeneity, and the random-effects model was adopted for pooled analysis, otherwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In many advanced-stage cancer types, such as unresectable or metastatic melanoma [58,59], non-small cell lung cancer (NSCLC) [60], advanced renal cell carcinoma [61], metastatic squamous head & neck [62], and relapsed or refractory Hodgkin lymphoma [63] ICI is an approved anti-cancer treatment and yields high rates of tumor regression [64]. Also, in contrast to chemotherapy, ICI is administered in a single dose once in 2-6 weeks based on the medication and cancer type.…”
Section: Expert Opinionmentioning
confidence: 99%
“…In many advanced-stage cancer types, such as unresectable or metastatic melanoma [58,59], non-small cell lung cancer (NSCLC) [60], advanced renal cell carcinoma [61], metastatic squamous head & neck [62], and relapsed or refractory Hodgkin lymphoma [63] ICI is an approved anti-cancer treatment and yields high rates of tumor regression [64]. Also, in contrast to chemotherapy, ICI is administered in a single dose once in 2-6 weeks based on the medication and cancer type.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The interruption of PD-1 engagement by its ligand reinvigorates the immune system, allowing immune-mediated anti-cancer responses to resume, leading to marked clinical responses in some cancers ( 9 ). Anti-PD-1 and anti-PD-L1 antibodies such as nivolumab, pembrolizumab, cemiplimab, and atezolizumab, durvalumab, avelumab have shown promising results in several cancer types ( 10 , 11 ). Nivolumab and pembrolizumab have been approved as first-line agents in recurrent/metastatic HNSCC patients by the United States Food and Drug Administration (FDA) ( 7 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of Zeng et al. ( 54 ) indicated that the OS rate was prolonged by anti-PD-1/PD-L1, as well as PFS. Meanwhile, the authors also demonstrated that anti-PD-1/PD-L1 could greatly enhance the objective response rate (ORR) with fewer adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…But there are no trials simultaneously investigating the efficacy and safety of all five therapeutic options (avelumab, atezolizumab, cemiplimab, nivolumab, and pembrolizumab). To date, two traditional meta-analyses were conducted to explore the efficacy of anti-PD-1/PD-L1 treatments (includes nivolumab, pembrolizumab, and atezolizumab) vs. chemotherapy in patients with NSCLCs ( 54 , 55 ). And one NMA only assessed the difference in both efficacy and safety profiles among nivolumab, pembrolizumab, and atezolizumab in pretreated NSCLC patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%